Role of Psychiatrist in Consultation-Liaison Psychiatry for Burn Injury Patient - Rini Nahdarina; Hendy Muagiri Margono (Jurnal Psikiatri Surabaya, 2020)
Consultation-Liaison Psychiatry is sub specialistic in psychiatric as a connector in clinical service team, teaching and research in borderline between psychiatric and medical medicine/surgery science. Consultation-Liaison Psychiatry is the connector to all diagnoses, therapeutic, research and educational service which being done by psychiatrist in general hospital and as a bridge between psychiatrist and other specialists. Burn injury is one of the leading causes of death and disability in the world. Global Burden Disease’s study reported approximately 265.000 deaths happened every year. According to WHO, 238.000 peo- ple died due to burn injury in 2000 and 95% of the death happened in developing and low income countries. Burn injury can be a remarkable traumatic, psychologic, social and economic experience. Physiologic changes can cause symptoms, both organic and psychiatric, starting from anxiety, delirium to psychosis. Psychiatric relation team can contribute substantially in order to manage this problem.